Marianna Gula, Mária Kurdi, István D. Rácz, eds. The Binding Strength of Irish Studies. Festschrift in Honour of Csilla Bertha and Donald E. Morse. Debrecen: Debrecen UP, 2011. 309 pages. - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
-